Carbon Emissions and Net Zero Under Carbon Capture, Usage and Storage (CCUS) Technology - Babu, A Mahesh; Akhil, Barapati; Pochampally, Naveen Kumar (International Journal of Advanced Science Computing and Engineering, 2023)
The key change in the environment is the gases which emit into the atmosphere and majorly carbon emissions by urbanization with greatly reduced energy needs through efficiency gains such that the balance of energy needs can be supplied with renewable technologies. According to various estimates, carbon stock consumes 30 to 40% of all energy resources. As the result, it is possible to get carbon dioxide atmosphere emissions reduction due to energy consumption reduction. In this research, we had a sample of current generation low-energy consumption and carbon storage by different techniques and usage by renewable sources, progress towards CCUS Technology.The way the zero-energy co2 goal is defined affects the choices designers to make achieve for this goal and whether they can claim success. CCUS will also support the transition from Blue Hydrogen to Green Hydrogen by accelerating the demand growth and creating technologies and infrastructure for the production, storage and transportation of hydrogen. Conversion of co2 to usable chemicals and products will spur economic development and help achieve some of the SDGs like green aggregates, green ammonia and methanol and ultimately green energy. This study shows the design impacts of the definition used for CCUS and progressed goals towards CCUS goals.